2021
DOI: 10.1016/j.obmed.2021.100333
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of fasting hyperglycemia in patients with COVID-19 – Diagnostic test accuracy meta-analysis

Abstract: Aims This meta-analysis aimed to assess the prognostic value of fasting hyperglycemia in patients with COVID-19. Methods A systematic literature search on PubMed, Embase, and Scopus were performed up until February 18, 2021. Fasting hyperglycemia was defined as fasting plasma glucose level above the reference value. The outcome of interest was poor outcome, which was a composite of mortality and severe COVID-19. The effect estimate was in odds ratio (OR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In keeping with these results, some latest meta-analyses and studies showed sufficient data regarding the topic ( 109 112 ). The first one demonstrated associated DM and hyperglycemia in 19.70% (CI: 10.93-32.91) and 25.23% (CI: 19.07-32.58) of COVID-19 cases, respectively ( 110 ).…”
Section: Metabolic Outcomes Of Covid-19supporting
confidence: 61%
“…In keeping with these results, some latest meta-analyses and studies showed sufficient data regarding the topic ( 109 112 ). The first one demonstrated associated DM and hyperglycemia in 19.70% (CI: 10.93-32.91) and 25.23% (CI: 19.07-32.58) of COVID-19 cases, respectively ( 110 ).…”
Section: Metabolic Outcomes Of Covid-19supporting
confidence: 61%
“…In the present study, the association with severe COVID‐19 progression was weaker for higher RPG than for higher HbA1c level on admission (Table 3). Although previous meta‐analyses have shown fasting plasma glucose level to be associated with COVID‐19 prognosis 36,37 , no such findings have shown a robust association of admission RPG level 36 . Determination of fasting plasma glucose rather than RPG at the time of admission might be more important for predicting the prognosis of COVID‐19, as well as analysis of the association of HbA1c or plasma glucose level in affected patients.…”
Section: Discussionmentioning
confidence: 98%
“…The finding of lower soluble DPP-IV receptor in COVID-19 in compare to healthy subject might also indicates the role of DPP-IV in facilitating viral entry although the exact interactions between DPP-IV and coronavirus and how it influence the viral entry has not been established [ [59] , [60] , [61] ]. However, since poor glucose control, cytokine storm, and multiorgan dysfunction have been established as a risk factor for worse outcome [ 40 , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] ], one might consider the benefit of excellent glucose control, cardiorenal effect and inflammatory modulation of DPP-IV inhibitor as an potential drug in treating T2DM patient with COVID-19 [ 5 , 75 ].…”
Section: Discussionmentioning
confidence: 99%